Retramatização e a pesquisa de papéis familiares: os avós - Batista, Marcia Almeida (2012)
This is a thorough analysis of re-plotting, a sociodramatic working method developed by Arnaldo Liberman, looking at the potential of this method in the research of contemporary roles, with particular emphasis on the role of grandparents. Despite of being widely used by psychodramatists, we couldn t find references in the literature with regards the potential of re-plotting, and as we consider it to be an appropriate instrument for research, our aim is to conduct a thorough analysis of this working method. The reason we chose to explore the role of grandparents is that there is significantly less research of these in comparison to the parental roles, and with the aging of the population the chances of people experiencing these roles have increased. We have analysed a re-plotting session that took place during a public psychodrama act, comparing the information obtained from this event with information from the relevant literature, and evaluating the actual process of replotting through which this information was gathered. It was shown that the grandparent role is a role linked with elderly people who give their grandchildren a sense of importance and self-worth, and allow them to feel part of a family history with the acknowledgement of their ancestry. It was also shown that through the use of re-plotting a wide range of information can be gathered about the explored roles, also allowing a comparison of individual and collective concepts. Furthermore, through group members reflections on the information obtained during the process, this method can also promote wellbeing. In certain situations it also makes psychotherapeutic or axiodramatic work possible